A CPW‐fed UWB MIMO antenna with integrated GSM band and dual band notches. Issue 1 (10th October 2018) - Srivastava, Kunal; Kumar, Ashwani; Kanaujia, Binod K.; Dwari, Santanu; Kumar, Sachin
Abstract: This article presents a coplanar waveguide fed global system for mobile communications band integrated ultra wide band (UWB) multiple input multiple output (MIMO) antenna with single and dual notch band characteristics. The novelty of the antenna lies in its design as all the unit cells of the proposed UWB MIMO antenna structure are orthogonal to each other therefore the additional isolation elements responsible for achieving high isolation are not required consequently making proposed antenna design simple and easy to fabricate. In this context, 2 MIMO systems have been designed. The first MIMO system is consisting of a dual port antenna whereas the second MIMO system is a printed quad port antenna; further single and dual notch band are achieved in the proposed multi‐port MIMO antenna. The antenna shows pattern diversity throughout the impedance bandwidth range. The gain of the antenna varies from 4 to 8.48 dBi. The 2 band notches are achieved at 4.8 and 7.7 GHz in the UWB range. The proposed antenna is fabricated and it is found measured results are in good agreement with simulated results.